2015
DOI: 10.7863/ultra.34.7.1253
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Sonography Training Into Undergraduate Medical Education

Abstract: Point-of-care sonography is inconsistently taught in medical school. The interns in our study also thought that sonography education should begin in medical school, and sonography should be taught by using simulation and at the bedside.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…However, the epidemiology of diseases and facilities available within the Middle East vary significantly from those in other regions [25][26][27]. Medical schools worldwide have integrated POCUS into their curricula [24]. However, there is currently no consensus on the need for POCUS training during the internship year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the epidemiology of diseases and facilities available within the Middle East vary significantly from those in other regions [25][26][27]. Medical schools worldwide have integrated POCUS into their curricula [24]. However, there is currently no consensus on the need for POCUS training during the internship year.…”
Section: Discussionmentioning
confidence: 99%
“…Studies describing the applications of POCUS and the competencies required for its safe practice were reviewed [1,3,[10][11][12][13]16,23,24]. Drawing on this knowledge, two researchers with expertise in medical education, POCUS, and survey design (RR and AH) developed a validated questionnaire to investigate interns' perceptions of POCUS.…”
Section: Questionnaire Developmentmentioning
confidence: 99%
“…In another study, Turner et al compared two groups that used and did not use a simulation device during their ultrasound training in terms of manner, confidence, knowledge, and skill levels after training and found the results of the group that received ultrasound training with the simulation-based device to be better in every category [ 16 ]. In studies evaluating centers in USA that provide ultrasound training, although it was reported that each center has a different training program, some centers follow the traditional curriculum while others follow the formal curriculum, and there is no consensus on training times and manners, it was found that ultrasound training was performed with the support of simulation-based devices in all these centers [ 17 - 20 ]. In our study, we supplemented the theoretical training provided to the students with the simulation-based practical training.…”
Section: Discussionmentioning
confidence: 99%
“…Several international medical faculties have implemented US course components into their core curriculum [8], [9], [10], [11], [12], [13], [14], [15], [16]. In 2011, Hoppmann et al integrated a vertical US curriculum at the University of South Carolina, School of Medicine for all medical students across four years of medical school [8].…”
Section: Introductionmentioning
confidence: 99%